Modulation of Pathological Pain by Epidermal Growth Factor Receptor - Borges, Jazlyn P.; Mekhail, Katrina; Fairn, Gregory D.; Antonescu, Costin N.; Steinberg, Benjamin E. (Frontiers in Pharmacology, 2021)
Chronic pain has been widely recognized as a major public health problem that impacts multiple aspects of patient quality of life. Unfortunately, chronic pain is often resistant to conventional analgesics, which are further limited by their various side effects. New therapeutic strategies and targets are needed to better serve the millions of people suffering from this devastating disease. To this end, recent clinical and preclinical studies have implicated the epidermal growth factor receptor signaling pathway in chronic pain states. EGFR is one of four members of the ErbB family of receptor tyrosine kinases that have key roles in development and the progression of many cancers. EGFR functions by activating many intracellular signalling pathways following binding of various ligands to the receptor. Several of these signalling pathways, such as phosphatidylinositol 3-kinase (PI3K), are known mediators of pain. EGFR inhibitors are known for their use as cancer therapeutics but given recent evidence in pilot clinical and preclinical investigations, may have clinical use for treating chronic pain. Here, we review the clinical and preclinical evidence implicating EGFR in pathological pain states and provide an overview of EGFR signalling highlighting how EGFR and its ligands drive pain hypersensitivity and interact with important pain pathways such as the opioid system.